Fandomization on the internet a study on Filipino KPop fans' online productivity - Chavez, Mary Grace Louise Garduce 1992-; Manalili, Perlita G.; University of the Philippines. College of Mass Communication (2014)
"This study is about the online productivity of the Korean POP (KPOP) fans in the Philippines. Cassiopeia Philippines, one of the biggest and pioneering fan clubs in the Philippines, served as the case study in this research. The study used the combined concepts of Jenkins' Convergence Culture and Consumer Activism, Fiske's Fan Productivity and Dahlgren's Parameters of Online Participation. Participation, interactivity and fan labor were the three variable determined and served as a guide in this study. The researcher conducted online observation and focus interviews to four (4) Filipino KPOP fans that are members of the Cassiopeia Philippine fan club. The study found out that internet plays an important role in the maintenance and progress of the growing KPOP fandom in the Philippines. The Philippin KPOP fandom is highly aware of the power of the internet and they are also knowledgeable of how to make use of this power in their favour. Thus, the Filipino KPOP fans utilized the internet in participating, interacting and producing new texts in the KPOP fandom. The productivity of Philippin KPOP fandom is significantly visible online and this productivity has moved past the walls of the visual fan community and into the real world."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Popular music -- Korea; Fan clubs -- Philippines; Online social networks -- Philippines; Consumer movements -- Philippines; Cassiopeia Philippines (Online community).